Sclerosing Polycystic Adenosis of the Parotid Gland: Report of a Bifocal, Paucicystic Variant with Ductal Carcinoma in situ and Pronounced Stromal Distortion Mimicking Invasive Carcinoma - Petersson, F. (2016)
10.1007/s12105-011-0242-6